2019
DOI: 10.3892/ijo.2019.4754
|View full text |Cite
|
Sign up to set email alerts
|

MYB promotes the growth and metastasis of salivary adenoid cystic carcinoma

Abstract: The incidence of recurrent t(6;9) translocation of the MYB proto-oncogene to NFIB (the gene that encodes nuclear factor 1 B-type) in adenoid cystic carcinoma (ACC) tumour tissues is high. However, MYB [the gene that encodes transcriptional activator Myb (MYB)] overexpression is more common, indicating that MYB serves a key role in ACC. The current study aimed to investigate the role of MYB in salivary (S)ACC growth and metastasis. A total of 50 fresh-frozen SACC tissues and 41 fresh-frozen normal submandibular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
34
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 53 publications
6
34
0
3
Order By: Relevance
“… 28 , 29 In recent years, many studies have also found that MYB can regulate cancer progression. 30 , 31 Zhang et al showed that MYB was highly expressed in OC and could promote epithelial–mesenchymal transition and cisplatin resistance in OC. 32 Furthermore, previous studies also indicated that MYB overexpression could promote OC proliferation, invasion and cisplatin resistance by activating NF-κB/STAT3 pathway.…”
Section: Discussionmentioning
confidence: 99%
“… 28 , 29 In recent years, many studies have also found that MYB can regulate cancer progression. 30 , 31 Zhang et al showed that MYB was highly expressed in OC and could promote epithelial–mesenchymal transition and cisplatin resistance in OC. 32 Furthermore, previous studies also indicated that MYB overexpression could promote OC proliferation, invasion and cisplatin resistance by activating NF-κB/STAT3 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] The high expression of MYB mRNA might explain the high frequency of metastasis from tumours of the major salivary gland, especially those of the submandibular gland. 22,23 In our study, 54 (54/77) primary cases showed positivity for S100, but seven of nine metastatic cases showed negativity for S100 (7/9) (p = 0.013). A plausible reason for the lack of S100 expression is the absence of myoepithelial cells or the lack of expression of S100 proteins despite the presence of myoepithelial cells.…”
Section: Discussionmentioning
confidence: 40%
“…Myb, a membrane protein, is overexpressed in 60-80% of cases of ACCs, usually correlated with a genetic translocation of the MYB gene to the transcription factor gene NFIB, resulting in the MYB-NFIB fusion, an important oncogene (t [6,9] ). This fusion has been postulated as the main driver of tumor proliferation in ACC (87,88). A MYB oncogene fusion, through Akt and mitogenactivated protein kinase (MAPK) signaling pathways, activates the expression of NSR, MET, EGFR, IGF1R, and specifically IGF2.…”
Section: Myb-nfib Pathwaymentioning
confidence: 99%